Phase I study of imalumab (BAX69), a fully human recombinant antioxidized macrophage migration inhibitory factor antibody in advanced solid tumours. Issue 9 (12th April 2020) - Mahalingam, Devalingam; Patel, Manish R.; Sachdev, Jasgit C.; Hart, Lowell L.; Halama, Niels; Ramanathan, Ramesh K.; Sarantopoulos, John; Völkel, Dirk; Youssef, Ashraf; de Jong, Floris A.; Tsimberidou, Apostolia Maria
Abstract : Aim: Preclinical evidence suggests that oxidized macrophage migration inhibitory factor (oxMIF) may be involved in carcinogenesis. This phase 1 study (NCT01765790) assessed the safety, tolerability, pharmacokinetics and antitumour activity of imalumab, an oxMIF inhibitor, in patients with advanced cancer using '3 + 3' dose escalation. Methods: In Schedule 1, patients with solid tumours received doses from 1 to 50 mg/kg IV every 2 weeks. In Schedule 2, patients with metastatic colorectal adenocarcinoma, non‐small‐cell lung, or ovarian cancer received weekly doses of 10 or 25 mg/kg IV (1 cycle = 28 days). Treatment continued until disease progression, unacceptable toxicity, dose‐limiting toxicity, or withdrawal of consent. Results: Fifty of 68 enrolled patients received imalumab. The most common treatment‐related adverse events (TRAEs) included fatigue (10%) and vomiting (6%); four grade 3 serious TRAEs (two patients) occurred. The dose‐limiting toxicity was allergic alveolitis (one patient, 50 mg/kg every 2 weeks). The maximum tolerated and biologically active doses were 37.5 mg/kg every 2 weeks and 10 mg/kg weekly, respectively. Of 39 assessed patients, 13 had stable disease (≥4 months in 8 patients). Conclusions: Imalumab had a maximum tolerated dose of 37.5 mg/kg every 2 weeks in patients with advanced solid tumours, with a biologically active dose of 10 mg/kg weekly. Further investigation will help define the role of oxMIF as a cancer treatment target.